PERBANDINGAN NILAI HEMATOKRIT DARAH VENA METODE AUTOMATIK DAN DARAH KAPILER METODE MIKRO HEMATOKRIT - Maria Nuraeni (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Hematology examination aims to establish the diagnosis, supporting the early alert system, monitoring treatment,maintaining health, and preventing disease. Hematocrit is a hematological examination with venous blood orcapillary blood. Increased hematocrit value has a diagnostic significance to detect, dengue hemorrhagic fever.Decreased hematocrit is an indicator of anemia, leukemia, or hyperthyroidism.Hematocrit examination can use theautomatic method with a hematology analyzer or microhematocrit with a centrifuge. The examination material canuse venous blood or capillary blood.Through descriptive analytic research, want to know the comparison of venousblood hematocrit values using an automatic hematology analyzer KX.21 and capillary blood using centrifuge. Dataanalysis usesindependent t test. The results showed that the average hematocrit value of capillary blood bymicrohematocrit method 42%, higher than venous blood samples by automatic method, which 41%. T independenttest results obtained p value: 0.383 greater than 0.05 values (p: 0.383> 0.05). There was no difference meanhematocrit values from venous blood by automatic method and capillary blood by microhematocrit method.Bothsample types and methods did not affect the measurement of erythrocyte volume in 100 ml of blood